The complete paternally inherited mitochondrial genomes of three clam species in genus Macridiscus (Bivalvia: Veneridae): A TDRL model of dimer-mitogenome rearrangement of doubly uniparental inheritance - Wang, Rui; Li, Xuanzhao; Qi, Jiwei (Frontiers in Marine Science, 2022)
One of the most striking exceptions to strict maternal inheritance of mitochondrial DNA (mtDNA) in the animal kingdom is a system called doubly uniparental inheritance (DUI), which exists in several bivalve species. DUI is characterized by the presence of two distinct sex-associated mitochondrial lineages: one transmitted through eggs (F-type mtDNA) and the other through sperm (M-type mtDNA). Presently, most known species exhibiting DUI belong to the freshwater bivalve order Unionoida. Other groups with species exhibiting DUI include the orders Mytiloida, Veneroida, and Nuculanoida. In Veneroida, the complete M-type mtDNA is available for two species. We report the presence of DUI in three species belonging to genus Macridiscus (Macridiscus melanaegis, Macridiscus multifarious, and Macridiscus semicancellata), in the order Veneroida, further obtaining their complete M-type mitogenomes. The M-type mitogenome sizes for M. melanaegis, M. multifarious, and M. semicancellata were 19,019 bp, 18,694 bp, and 18,726 bp, respectively, and the mean nucleotide difference between M-type and F-type mitogenomes was 21–23%. We compared the M-type and F-type mitogenomes, and found that they show roughly the same genome features, except for gene order. In phylogenetic analyses of Veneroida, a “gender-joining” pattern was revealed within Macridiscus, similar to the pattern of “partial” Mytilus complex (except Unionida). This new insight provides novel evidence supporting the theory that Veneroida and Mytiloida have a more similar DUI pattern than Unionida. A large-scale rearrangement between the sex-linked mitogenomes of the three Macridiscus species was reported. From the observed rearrangement patterns, gene rearrangement between the two sex-linked mitogenomes could be explained by the tandem duplication and random loss (TDRL) model of dimer-mitogenome. This is the first report of heterogeneous genomes with two types of large-scale arrangements in the same organism, and may be contribute significantly to the study of mitochondrial recombination mechanisms.